Patterns of spatial distribution, diel activity and human-bear conflict of Ursus thibetanus in the Hindu Kush mountains, Pakistan - Ahmad, Faizan (2022)
The Asiatic black bear (Ursus thibetanus) is an elusive mammal and its conservation is currently a challenge in Pakistan due to the negative interaction with human communities and habitat fragmentation. We investigated the distribution, activity pattern and human-bear conflict of the Asiatic black bear in the Hindu Kush, a major mountains system in Pakistan. Our study was conducted from October 2020 to December 2020 in the Bahrain Valley, placed in the southeastern area of the Hindu Kush. We firstly carried out a preliminary sign survey for the bear's presence and, then, we installed an infrared sensor camera traps in the potential suitable habitat for the bear, 23 locations for 152 trap nights, to monitor its activity. Furthermore, to understand human-bear conflict, a questionnaire survey was submitted to 107 local people living in the bear’s habitat. The Asiatic black bear was photographed in 12 camera stations with 60 different capture events. We obtained a trap success percent of 64.8% between 2,100 m - 2,400 m above the sea level while the total trap success calculated for the whole camera trapping survey of the bears was 39.5%. The bears showed a bimodal activity pattern with peaks just after sunset and during the night (88% of observations from 00:00 to 06:00 and 18:00 to 24:00). We observed that the female and male bears and their puppies were not hibernating in subzero temperatures until December. Local communities had concerns over livestock and crops losses in the area. Our findings showed once again that the Asiatic black bear urgently needs effective management plans to guarantee its conservation in Pakistan.